Antagonistic, synergistic and interaction effects of process parameters during oxygen delignification of Melia dubia kraft pulp. (20th October 2018) - Anupam, Kumar; Deepika,; Swaroop, Vinay; Lal, Priti Shivhare
Abstract: Melia dubia is a recently identified hardwood for papermaking. This study reports oxygen delignification of its kraft pulp. Modeling of O2 delignification was done implementing central composite design taking temperature, time and NaOH charge as process parameters while pulp yield, kappa number, intrinsic viscosity and brightness were the process outputs. The high precision quadratic models developed for O2 delignification revealed antagonistic, synergistic and significant interaction effects between temperature, time and NaOH charge. The optimum values of process parameters estimated were 90 °C, 90 min and 1.39% respectively which gave pulp yield 96.64%, total kappa number 10.52, intrinsic viscosity 628.54 cm 3 /g and brightness 42.52% which were very much comparable to other papermaking raw materials. On the whole, the optimization desirability obtained for O2 delignification was 0.621. The overall O2 delignification efficiency based on the total kappa number and the true lignin kappa number was found to be 30.33% and 38.23% respectively. The O2 delignification practiced in this investigation led to 10.42% increase in brightness and 19.93% reduction in viscosity which would prove advantageous for subsequent elemental and total chlorine free bleaching. Highlights: First such report on oxygen delignification of kraft pulp from Melia dubia . Modeling of oxygen delignification using five level central composite design. Pulp yield, kappa number, viscosity and brightness as key process outputs. Temperature, time and alkali charge interactions during oxygen delignification. Comparison of oxygen delignification of M. dubia pulp with other raw materials.